Influence of swimming athletes’ sports psychological fatigue on sports performance - Zhan, Yejun; Xue, Wei (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study aims to examine the influence of swimming athletes' sports psychological fatigue on sports performance in China. The subjects selected for this study are active swimmers participating in competitions. Eighty questionnaires were issued during this study's investigation, with a 100 % recovery rate. The PES-T was used to assess emotion before to competition. The data was collected using literature research, questionnaire, interview, data statistics, logical analysis, personality questionnaire (EPQ), and representative questions from the 90-item symptom self-rating scale. (SCL90). All parameters of exercise-induced mental exhaustion, training and competition satisfaction in swimmers obtained a significant connection (p<0.05) and had a significantly negative correlation regression model overall test F (p<0.05), and their impact is negative. The two predictive factors effectively accounted for 41.5% of the variance in training and Competition Satisfaction, and both impacts were negative. It is crucial to increase the competitive performance of swimmers to enhance the performance of athletes more effectively and stimulate the creation of sports memory. It is necessary to enhance the theoretical system of swimming sports psychological training further to improve the theoretical system of swimming sports psychological training, assist swimmers in effectively controlling and relieving sports psychological fatigue, and enhance training effect and competition results. Consider psychological choices carefully. Trait anxiety is a stable personality trait and a favorable predictor of psychological exhaustion in sports. One of the psychological selection indications for swimmers can be trait anxiety.